Desenvolvimento e validação de um modelo de referência para a gestão estratégica do desempenho de parques tecnológicos - Juliane de Almeida Ribeiro (2017)
The ventures known as technology parks have spread all over the world as linking organizations between universities, business and government, playing a key role for the activation of the Triple Helix. The main objectives of technology parks are: boost innovation; and promote institutional cooperation between the actors involved, the transfer of technologies, the consolidation of technology based-firms and regional socioeconomic development. In Brazil, these ventures had evolved over the last years, notwithstanding difficulties as: expansion and improvement of physical infrastructure, technology-based business attraction and the establishment of performance evaluation systems. In a global context, after a period of intensive dissemination of technology parks, it is notable the concern about the development of reference models for the management and performance evaluation of these ventures, capable to represent the main actors involved, to prove the achieved results and to indicate improvement opportunities. Although proposals have emerged on the literature in the last years, there is no agreement about a systematic model to understand technology parks, identify the nature of their performance and compare the results of different existing initiatives. Taking in account this literature gap, this work proposes a reference model for the strategic performance management of technology parks, built from the theoretical basis of the service-dominant logic (S-DL), the managerial tool Balanced Scorecard (BSC) and the premises for scale and model construction of the general hierarchical model (GHM). With the support of an exploratory and qualitative study of three technology parks in operation in Brazil, data from the performance of their strategic planning and management were obtained. These data were analyzed by the thematic category technique, which approached the critical success factors for technology parks, the main value-added services offered, the most important performance indicators and the strategic objectives of these innovation environments. These elements supported the proposition of a hypothetical-conceptual model based on the S-DL, the BSC and the GHM and adapted to the technology parks context, composed by five dimensions, hierarchically organized: learning & growth, internal processes, tenant companies, scientific, technology & innovation development and sustainable socioeconomic development. The scales elaborated for the construct operationalization supported the creation of an electronic questionnaire sent to managers and directors of more than 500 companies installed in various Brazilian technology parks. From the 84 valid responses obtained in this transversal survey, data were analyzed with descriptive and multivariate statistical techniques, especially exploratory and confirmatory factor analysis, through the utilization of structural equation modeling. Considering the results, the five constructs proposed and 21 of the 48 indicators elaborated were validated. Five from the ten model related hypothesis were confirmed. The validated model revealed the importance of resource integration from the different actors involved to the maximization of value cocreation in these environments. It is expected that this model, which can be improved in future studies, help technology parks managers and stakeholders in the institutionalization of management tools and performance evaluation, as well as in the identification of best practices and improvement opportunities, in order to enhance the success of these ventures.